Whorfian Effects in Color Perception: Deep or Shallow? - Elisabetta Lalumera (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
This paper discusses, from the point of view of the philosophy of psychology, recent behavioral and brain studies showing effects of the diversity of language vocabulary on color perception. I examine the alternative between two different interpretations of these so-called whorfian effects, namely habitual or deep whorfianism, and shallow whorfianism. I argue that at the moment the evidence underdetermines both interpretations and the question is open. I also clarify that shallow whorfianism is not a synonym for ‘trivial whorfianism’, as some authors have suggested, but rather makes a case for the online and situated nature of human cognition.
Keywords: color perception; whorfianism; philosophy of psychology; cognitive differences